School Readiness for Early Childhood in Face-To-Face Learning in Pandemic Covid-19 - Oktavianingsih, Eka; Arifiyanti, Nurul (Indonesian Journal of Educational Assessment, 2021)
Face-to-face (FTF) learning has to be implemented during COVID-19 due to many recent study reported that online learning was ineffective. Re-opening school in early childhood education also requires a lot of preparation from schools, children, and parents. This paper aims to provide a clearer picture of early childhood education readiness and give the future recommendation in preparing reopening schools during COVID-19 pandemic. Data were collected through in-depth interviews with seven teachers from seven early childhood education who were selected by purposive sampling technique. Then, the transcript data was analyze using Interpretative Phenomenology Analysis to build the categories and themes. The findings are six main themes about school readiness emerged: teacher perceptions about FTF learning during COVID-19, school policies about learning during COVID-19, teacher readiness in FTF learning during COVID-19, school facilities, communication with parents about FTF learning during COVID-19, and learning assesment during FTF learning. The implication of this study is discussed in this paper.